La notion de « terrain(s) » dans la formation des futurs enseignants en langues-cultures - Séverine Behra; Dominique Macaire (Recherches en didactique des langues et des cultures)
In the field of foreign languages and cultures, the notion of “terrain” is multifaceted. The “terrain”, considered as a social construct, is both a delimited educational space and a field of practice. In this specific meaning, the “terrains” are not only hosting practices, but they also produce and legitimise them, with their own dynamics. The various uses of the notion of "terrain” reveal some ideologies underlying languages-cultures and their teaching and learning. Thus, it has significant implications for the teacher education. As a point of main interest in the pre-professionalisation ecology, our contribution examines three types of “terrains” that future primary teachers come into. Our questions consider the (foreign) languages and cultures at school in relation to the school language and the home languages because their cohabitation is not always that facilitated. In such a context, the question is to better understand to what extend the notion of “terrains” contribute to pre-professionalisation? Can we then better link together the contributing “terrains” of a teacher education supporting foreign languages and cultures to make it more relevant to languages and cultures in their diversity.